Mitral valve restenosis after closed mitral commissurotomy: case discussion - Xu, Anyi; Jin, Jiang; Li, Xiaodong; Xiao, Jian; Zhu, Peng; Gong, Wenhui; Liu, Yue; Yu, Yuetian; Wang, Chunguang; Zhang, Chengxin; Hameed, Irbaz; Salemi, Arash; et al. (Journal of Thoracic Disease, 2019)
At the beginning of heart valve surgery, closed mitral commissurotomy (CMC) and balloon dilatation were widely applied, but they were gradually replaced by mitral valvuloplasty or replacement due to their poor long-term effectiveness (1). Valve calcification/contracture and restenosis often occur after CMC or balloon dilatation, along with the lesions in the untreated valves and cardiac insufficiency (2). A re-operation is often required. With the development of bioprosthetic valve replacement and valvuloplasty, re-operation of valves in China is gradually increasing (3). Whether an open surgery or a thoracoscopic surgery should be performed remains controversial. In this manuscript, we present a case of mitral restenosis and calcification 30 years after CMC. The invited multidisciplinary experts gave detailed suggestions on intra- and post-operative monitoring and treatment.